Efficacy and Safety of Endoscopic Resection for Small Gastric Gastrointestinal Stromal Tumors in Elderly Patients - Changzhou Cai; Jinpu Yang; Mengting Ren; Lu Lv; Xinxin Zhou; Mosang Yu; Feng Ji (Gastroenterology Research and Practice)
Background. Gastrointestinal stromal tumors (GISTs) are prevalent in elderly patients. Endoscopic resection has become popular for treating small (≤5 cm) gastric GISTs. However, little is known about the outcomes of endoscopic resection in elderly patients. Aim. To assess the efficacy and safety of endoscopic resection for small (≤5 cm) gastric GISTs in elderly patients (≥65 years old). Methods. A total of 260 patients (265 lesions) with gastric GISTs treated via endoscopic resection from January 2011 to May 2020 were retrospectively analyzed. Among them, 65 patients were ≥65 years old (elderly group), and 195 patients were <65 years old (nonelderly group). Clinicopathological characteristics, postoperative complications, and tumor recurrence rates between the two age groups were compared. Results. A total of 260 patients with primary small (≤5 cm) gastric GISTs were treated with endoscopic resection. The median ages of the elderly and nonelderly groups were 68 (range 65-83) years and 55 (range 32-64) years, respectively. Elderly patients showed a higher incidence of comorbidities compared with nonelderly patients (61.5% versus 32.3%s, respectively; p<0.001). All elderly patients and 99.0% of nonelderly patients underwent en bloc resection; only two nonelderly patients received piecemeal resection. No significant differences were found regarding postoperative complications or tumor recurrence rates between the two groups. Conclusions. Although elderly patients had more comorbidities than nonelderly patients, both groups had similar postoperative complications and recurrence rates. We suggest that endoscopic resection performed by experienced endoscopists is safe and effective for treating small (≤5 cm) gastric GISTs in elderly patients.